Art therapy as a method of spiritual support for patients in clinical practice - Lazorko, Olha; Fedoova, Tetiana (Psychological Prospects Journal, 2022)
Purpose. The article determines the place of spiritual support of patients by art therapy methods in the system of professional care in clinical settings. Important tasks are the analysis of recent research on the spiritual support of patients in clinical practice; generalization and systematization of the main methodological approaches and review of applied research on the stated issues; explication of the categorical apparatus; substantiation of contemporaneous models of spiritual support of patients in art-therapeutic interaction; identification of psychotherapeutic targets of spiritual support of patients in the art-therapeutic process. Methods. This article has the character of theoretical and methodological research. The main research methods are the analysis of the latest research on the spiritual support of patients in clinical practice with the help of art therapy tools; synthesis, generalization and systematization of basic methodological approaches and applied research; explication of the categorical apparatus; theoretical and methodological modeling. Results. A review of foreign and domestic scientific publications allows us to conclude that the spiritual support of patients during recovery in the clinic is a fundamental condition for rapid recovery of patients regardless of diagnosis and course of disease. Art therapy as a method of spiritual support for patients in clinical settings has a high potential for application and requires further study, testing and implementation in the hospital. Conclusions. We have defined spiritual support as the therapeutic help for patients to find meaning, hope and integrity in their lives and relationships, to feel their connection with themselves, others and the universe, and to give them a sense of care, compassion and unconditional acceptance, readiness to be together in difficult times, listen to and respect their individual spiritual beliefs. We have identified psychotherapeutic targets for which spiritually oriented art therapy is effective: self-realization and self-development, self-knowledge, acceptance of reality, search for meaning and purpose of existence and awareness of self-worth. The purpose of the analysis of scientific sources allowed to determine the main models of modern art therapy based on spiritual support: Model of the continuum of expressive therapy; Recovery model; Body mind model in art therapy. An important task today is to find effective tools for art-therapeutic work and create programs of spiritual support for patients, which, of course, is a promising area of ​​further research.